2008
DOI: 10.2137/145960606778644485
|View full text |Cite
|
Sign up to set email alerts
|

Weed occurrence in Finnish coastal regions: a survey of organically cropped spring cereals

Abstract: Weed communities of organically cropped spring cereal stands in the southern and the northwestern coastal regions of Finland (= south and northwest, respectively) were compared with respect to number of species, frequency of occurrence, density and dry weight. Regional specialization of agricultural production along with differences in climate and soil properties were expected to generate differences in weed communities between south and northwest. Total and average numbers of species were higher in the south … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…, 2011). However, increased total biomass of weeds in organic cropping was mainly explained by the success of E. repens , as reported also by Riesinger and Hyvönen (2006).…”
Section: Discussionsupporting
confidence: 60%
“…, 2011). However, increased total biomass of weeds in organic cropping was mainly explained by the success of E. repens , as reported also by Riesinger and Hyvönen (2006).…”
Section: Discussionsupporting
confidence: 60%
“…Most recent studies from northern Europe confirmed the local value of organic farming for arable flora (Riesinger and Hyvö nen, 2006;Hyvö nen, 2007), pollinators (e.g. Ekroos et al, 2008), and some bird species (Piha et al, 2007;.…”
Section: Organic Farmingmentioning
confidence: 85%
“…(2000) showed that the response of farmland birds to agricultural intensification had a time‐lag of about 8–10 years over England and Wales. However, as far as we are aware, evaluations of a time since transition effect on authentic farms in replicated landscapes have only been made by Riesinger & Hyvönen (2006), studying weed species composition (but see also Kleijn & van Zuijlen 2004).…”
Section: Introductionmentioning
confidence: 99%